2005
DOI: 10.1597/04-066r.1
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Stress in Infancy and Psychosocial Adjustment in Toddlerhood: A Longitudinal Study of Children with Craniofacial Anomalies

Abstract: Elevated levels of parenting stress during infancy may be stable through toddlerhood for families having a child with a CFA. The relation between parenting stress and child adjustment is likely to be reciprocal. These findings should be replicated with a larger sample and multiple informants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 13 publications
4
66
0
5
Order By: Relevance
“…Research on craniofacial conditions has also shown that lower levels of parenting stress are associated with better child adjustment (Krueckeberg and Kapp-Simon, 1993; Krueckeberg et al, 1993; Pope et al, 2005) and better parental health status (Coulter et al, 1991). Baker et al (2009) documented that positive, approach-oriented coping strategies were correlated with better parental adjustment for parents of children with cleft lip and palate.…”
Section: Single-suture Craniosynostosismentioning
confidence: 99%
See 2 more Smart Citations
“…Research on craniofacial conditions has also shown that lower levels of parenting stress are associated with better child adjustment (Krueckeberg and Kapp-Simon, 1993; Krueckeberg et al, 1993; Pope et al, 2005) and better parental health status (Coulter et al, 1991). Baker et al (2009) documented that positive, approach-oriented coping strategies were correlated with better parental adjustment for parents of children with cleft lip and palate.…”
Section: Single-suture Craniosynostosismentioning
confidence: 99%
“…Whether parent functioning is viewed primarily in terms of resilience or risk for poor outcomes, parents’ cognitive, affective, and behavioral responses to stressful events must all be considered (Patterson, 1983; Deater-Deckard, 1998; Crnic et al, 2005; Pope et al, 2005; Haskett and Willoughby, 2007; Kwon, 2007; Baker et al, 2009). Abidin’s (1992, 1995) model of parenting stress is a good example of a multifaceted approach, focusing on parental perceptions of and attributions about the child’s various characteristics, the quality of the parent-child and marital relationships, and parents’ roles and responsibilities.…”
Section: Single-suture Craniosynostosismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study used a resilience model and suggested that parents of children with cleft who used problem-focused coping and had high levels of social support reported less family impact and more positive adjustment to their child’s condition than those who used avoidance-oriented coping strategies and had lower levels of social support (Baker et al, 2009). Indeed, how families and parents cope with their child’s condition impacts their stress level (Pope et al, 2005). …”
mentioning
confidence: 99%
“…The aim of palate repair is to create a complete closure, having an intact hard and soft palate with a normal functioning velopharyngeal mechanism (18). Even when newborns with cleft deformities receive appropriate treatment, some still have facial deformity and speech impairment (19)(20)(21), which further increases the health care and familial burden of the disease (22). With the help of Speech and Language thera- pists it is possible to improve these patients' speech.…”
Section: Introductionmentioning
confidence: 99%